ANALISIS BUDAYA ORGANISASI BOARDING SCHOOL MADRASAH ALIYAH NEGERI INSAN CENDEKIA SAMBAS - Ilham; Luhur Wicaksono; Radiana, Usman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the analysis of organizational culture at the Boarding School of MAN IC Sambas. The form of research is a qualitative approach. The research participants numbered 9 people consisting of 7 men and 2 women with the criteria of the principal, vice principal (waka), TU, teachers, and students aged 17-52 years. The research participants were determined by purposive sampling. The research method is descriptive with observation, interview, and documentation techniques. Data collection tools include observation, interview guidelines, and documents. Data analysis goes through three stages, namely data collection, data reduction, and conclusions. The main findings of this study: The level of artifacts in the form of symbols that look like logos, quotations from the Qur'an and wise words, building architecture combined with local wisdom, and verbal and nonverbal language used to communicate; The applicable norms in the form of unwritten and written regulations are stated in the School Guidelines and Regulations book; The values adopted contain five important values, namely professionalism, integrity, cooperation, responsibility, and discipline; The basic beliefs and assumptions applied are in the form of statements stating that education plays a role as a means of forming good character and morals. The conclusion of this study is in the form of an analysis of organizational culture in madrasahs which is quite good. The implication of this study is that with a good organizational culture, it is expected to be able to maximize the quality of education at MAN IC Sambas